The Urgency of Socio-Legislation in Providing Legal Responsibilities of Marital Cheating - Fatwa, Ahmad Fajruddin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
The desire to accommodate marital cheating as a despicable act and against the law has not been properly accommodated in the law enforcement process, even though this has long been developing and has many victims in society. Offenders are often only considered despicable acts specific to the parties involved with the victim, limited to the scope of the household. In fact, according to the results of the study conducted in the writing of this paper, various legal responsibilities of actors have been well accommodated in Indonesian social norms, and possible to arrest actors from the perspective of legislation. Therefore, the study of actors cannot be reduced to only those that limit themselves to written legal provisions by using the paradigm of the legality aspect of legal sources in determining crimes and acts against the law alone. This paper proves that marital cheating is not just a despicable act prohibited by social norms but also shows the various court judgments that have been made in resolving the marital cheating dispute.